Monitoring Turbin Angin Menggunakan Smartphone Android - Randy Yonanda Pratama; Muldi Yuhendri (Universitas Negeri Padang, 2020)
Wind turbines function as producers of mechanical power to drive generators in wind power plants. One factor that needs to be considered in the operation of wind turbines is the maximum capacity of the generator. Wind turbines must operate below the generator rating so as not to cause damage to the generator. Therefore, the operation of the wind turbine needs to be monitored and controlled to keep it operating within the generator rating limits. In this paper a horizontal axis wind turbine monitoring sistem is proposed using an Android smartphone. Wind turbine monitoring includes wind speed and turbine rotation speed parameters. This parameter data is obtained from sensors that are processed with Arduino Mega 2560. Data from Arduino is sent via the Bluetooth HC-04 module to be displayed on an Android smartphone. The experimental results show that the proposed wind turbine monitoring system has worked well. This can be seen from the wind speed and turbine rotation data that is displayed on android is exactly the same as the data on the measuring instrument